Pengaruh Prokrastinasi terhadap Kecemasan Akademik Mahasiswa Pendidikan Ekonomi FKIP Universitas Halu Oleo - Yuniyarti Ahiri; Jafar Ahiri; Harjun Harjun; Muhammad Juwantho Lewa; Wahyu Muh. Syata; Ilhamurrahman M Hubaib (Educational Journal, 2026)
Academic anxiety is a serious psychological problem experienced by pre-service teachers that affects their academic abilities and readiness to become professional educators. This study aims to analyze the effect of procrastination on academic anxiety among students of the Economics Education Department, Faculty of Teacher Training and Education, Halu Oleo University, Kendari. The study employed a causal correlational quantitative approach involving 146 students in semesters 3 and 5, selected through proportionate stratified random sampling. Research instruments consisted of a procrastination scale (31 valid items, α=0.911) and an academic anxiety scale (28 valid items, α=0.897). Data were analyzed using descriptive statistics and simple linear regression. Results showed 46.6% of students had moderate procrastination levels, and 43.2% experienced moderate academic anxiety. Regression analysis confirmed procrastination has a positive and significant effect on academic anxiety (β=0.906, t=25.745, p<0.05) with a contribution of 90.6%. Higher student procrastination levels correspond to greater academic anxiety. This study emphasizes the importance of addressing procrastination as a primary strategy to reduce academic anxiety among pre-service teachers through systematic intervention programs such as group counseling and time management training.